(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article develops and substantiates a statistical model for analyzing labor migration flows in the Surxondaryo region and their impact on regional employment dynamics. The study proceeds from the assumption that labor migration in peripheral regions is not merely a demographic phenomenon but a structurally embedded economic process shaped by employment opportunities, income differentials, and institutional conditions of the local labor market. Using regional statistical indicators, the research conceptualizes migration flows as an endogenous factor influencing employment structure, labor supply elasticity, and sectoral reallocation of the workforce. The novelty of the study lies in integrating migration intensity variables into a regional employment model, allowing for the identification of both short-term and medium-term effects of labor outflows on local employment indicators. The results demonstrate that labor migration in Surxondaryo exhibits a dual effect: while outward migration temporarily reduces pressure on the local labor market, it simultaneously generates structural labor shortages in specific sectors, particularly agriculture and low-skilled services. The proposed statistical framework contributes to regional labor economics by offering an empirically grounded tool for assessing migration–employment interdependencies in developing regions.